2007
DOI: 10.1177/0093854807299462
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentally Violent Youths

Abstract: Psychopathy in adults has been well documented as a robust predictor of violence. Explanations for this relation have focused on the affective deficit that characterizes psychopathy. This study examined the relations among psychopathic traits, empathy, attachment, and motivations for violence in 51 incarcerated adolescent offenders. Psychopathy scores were related to both instrumental and reactive violence. Youths who were classified as instrumentally violent scored higher on psychopathy than those who were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(26 citation statements)
references
References 39 publications
(44 reference statements)
4
19
0
2
Order By: Relevance
“…Converging with the studies mentioned in the Introduction (Bowlby, 1944;Frodi et al, 2001;Flight & Forth, 2007;Bakermans-Kranenburg & Van IJzendoorn, 2009;Mack et al, 2011;Craig et al, 2013;Schimmenti et al, 2014), we found associations between psychopathy and insecure attachment. As stated in the introduction only two studies, Mack et al (2011) andCraig et al (2013), reported associations between facets of psychopathy and dimensions of current attachment in substantial samples.…”
Section: Discussionsupporting
confidence: 77%
“…Converging with the studies mentioned in the Introduction (Bowlby, 1944;Frodi et al, 2001;Flight & Forth, 2007;Bakermans-Kranenburg & Van IJzendoorn, 2009;Mack et al, 2011;Craig et al, 2013;Schimmenti et al, 2014), we found associations between psychopathy and insecure attachment. As stated in the introduction only two studies, Mack et al (2011) andCraig et al (2013), reported associations between facets of psychopathy and dimensions of current attachment in substantial samples.…”
Section: Discussionsupporting
confidence: 77%
“…Our hypotheses are based on previous studies examining the relationship between psychopathy and aggressive behaviour. The results of such research support the assumption about the significant correlation between psychopathy features and aggression because both constructs pertain to difficulties in impulse control [23]. …”
Section: Aim Of the Studysupporting
confidence: 69%
“…The presence of CU traits is particularly salient in understanding aggression, with research indicating that affective deficits are more clearly related to a cruel, instrumental form of aggression than are the behavioral features of the construct (Flight & Forth, 2007;Kahn, Frick, Youngstrom, Findling, & Youngstrom, 2012).…”
Section: Introductionmentioning
confidence: 99%